Studi perbandingan metode CAPM dan APT pada perusahaan sektor manufaktur yang terdaftar di Bursa Efek Indonesia periode 2008 – 2013 - Juwana, Caresa (Kajian Ilmiah Mahasiswa Manajemen, 2015)
The financial sector and the capital market plays an important role in the economic growth of a country. Indonesian capital market investors expect high returns due to economic growth in developing countries more rapidly than developed countries. Economic developmentwill give positive influence on the development of capital market. With the performance of the capital market that getting better, the need for security analysis will also increase. Parameters used by investors who use fundamental techniques in making investment decisions is the consideration of the expected return. Expected return calculations used to measure whether the expected returns of the securities are in accordance with the expectations of investors. Therefore, we need an accurate method to calculate the expected return of securities so that investors can determine the investment return that corresponds to the desired expectations. CAPM and APT are 2 methods are widely used in the calculation of expected return. In this study macroeconomic factors used in the calculation of the APT is JCI, USD exchange rate, inflation (monthly), and the risk free rate. This study compared the accuracy of both methods in calculating the expected return of manufacturing sector companies in the Stock Exchange in the period 2008 - 2014 The method used to perform Comparing of the two methods is the mean difference test, Davidson and Mckinnon, and posterior odds ratio. The results of this study stated that APT is a more accurate method in the calculation of expected return than CAPM. Of the mean difference test, Davidson and Mckinnon, and posterior odds ratios were conducted in this study produced that APT is a more accurate method than the CAPM in the calculation of expected return. It can be concluded that the APT is more accurate than the CAPM in a study conducted at the Indonesian Stock Exchange manufacturing sector in the period of 2008-2014.